(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Breve storia di un storia lunga - 2. La teologia giuridica di Hans Kelsen - 3. La teologia politica di Carl Schmitt - 4. Intermezzo - 5. Il lascito di Schmitt - 6. Il dito e la luna - 7. La religione del valore di Ronald Dworkin - 8. Una conclusione, … per iniziare. Glory and misery about political theology ABSTRACT. This paper deals with the interactions between religions and law. In particular, it analyses and discusses Kelsen’s, Schmitt’s, and Dworkin’s theories on legal and/or political theology. Although in different ways, these authors have well perceived a large number of links between religion and law; nevertheless their conceptions about religion are narrow and remains strictly Christian-centred. A wider concept of religion - as it has been conceptualized by anthropological and social studies - could reveals how many religious concepts underlie legal systems all over the world, and how much (Christian) religion is masked even in western secular law and institutions.